The Cycle of Verbal Violence Among Nurse Colleagues in South Korea. Issue 5 (March 2022) - Park, Su-Hyun; Choi, Eun-Hi
In Korea, suicide by nurses due to workplace verbal violence has become a serious social controversy. This study used a descriptive survey to identify factors influencing nurses' experiences with being either victims or perpetrators of verbal violence among colleagues. Participants were 205 nurses working at large-scale general hospitals in D city in August 2019. Data were collected through standardized questionnaires on experiences of verbal violence, committing acts of verbal violence, demographic characteristics, and job stress. For experiences of verbal violence, statistically significant differences were observed in age, gender, and nightshift work. Committing acts of verbal violence showed statistically significant differences in age, gender, entire career experience, career experience in one's present division, and nightshift work. A significant correlation was found between experiences of verbal violence, committing acts of verbal violence, and job stress. Gender and nightshift work influenced experiences of verbal violence in Model 1, while gender, nightshift work, and relationship conflicts were extracted in Model 2. In Model 3, career experience and committing acts of verbal violence were found to be significant. For committing acts of verbal violence, gender, nightshift work, and career experience were extracted in Model 1; gender, nightshift work, and relationship conflict were extracted in Model 2; and nightshift work, career experience, and experiences of verbal violence were significant in Model 3. Regarding verbal violence among nurses, a vicious cycle caused by job stress exists, in which newly hired nurses are often victims of verbal violence; however, as they gain career experience, they become the perpetrators. Therefore, to reduce nurses' job stress, it is necessary to operate job stress-control programs by career level, promote conversations among nurses to increase understanding of each other, and build a culture of mutual respect.